2012
DOI: 10.1021/ie300555f
|View full text |Cite
|
Sign up to set email alerts
|

MnOx–CeO2/Activated Carbon Honeycomb Catalyst for Selective Catalytic Reduction of NO with NH3 at Low Temperatures

Abstract: Activated carbon honeycomb supported manganese and cerium oxides (MnO x –CeO2/ACH) catalysts were investigated for selective catalytic reduction (SCR) of NO at low temperatures of 80–200 °C. Compared with ACH supported manganese oxide catalyst (MnO x /ACH), MnO x –CeO2/ACH catalysts show much higher SCR activity and higher selectivity to N2. NO conversion can be improved by the addition of CeO2 from less than 50% to 100% at 80–160 °C. The N2 selectivity of higher than 99.8% is obtained over the Ce(1)Mn/ACH cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 39 publications
4
64
0
Order By: Relevance
“…vacancy associates that have resulted in the intermediate decrease in the particle size. Furthermore, the result suggests the doping of Mn can efficiently inhibit growth of the cubic phase, which agrees well with the previous reports [20,21]. As the decrease in the grain size is conductive to the contact between catalysts and reactant gas flow [22], Mn dopant should have promotion effect on catalytic performance.…”
Section: Crystallographic and Morphological Structuresupporting
confidence: 90%
“…vacancy associates that have resulted in the intermediate decrease in the particle size. Furthermore, the result suggests the doping of Mn can efficiently inhibit growth of the cubic phase, which agrees well with the previous reports [20,21]. As the decrease in the grain size is conductive to the contact between catalysts and reactant gas flow [22], Mn dopant should have promotion effect on catalytic performance.…”
Section: Crystallographic and Morphological Structuresupporting
confidence: 90%
“…Several diffraction peaks observed at 28 (PDF#34-0394). The peaks attributed to CeO 2 could also be seen before and after the SCR reaction [25]. However, no manganese oxide phases could be detected, indicating that the manganese oxides formed as primary crystals of less than approximately 4 nm, which was consistent with the report by Machida et al [26].…”
Section: Xpssupporting
confidence: 90%
“…It can be found that the addition of CeO x to the 9%Mn/TiO 2 -0.8%GO had a negative effect on the specific surface area and the porous structure parameters, which has also been proven by some other analogous research [19,45,46]. When the ratio was no more than 0.3, this tendency was not very obvious, but when the Ce/Mn molar ratio reached 0.4, the specific surface area and total pore volume of the catalysts decreased significantly.…”
Section: Bet Surface Areas and Pore Size Distributionssupporting
confidence: 58%